ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETERSEDIAAN OBAT DI ERA JKN PADA RSUD dr. SOEDONO MADIUN - Prabowo, Pulung (Widya Warta, 2018)
The availability of drugs is essential closely related to the quality of care. The availability of drugs is the main thing in creating the satisfaction of patients, doctors, and pharmacy personnels. Good availability of drugs will create more efficient and effective budget. The purpose of this study was to determine whether the role of doctors, pharmacy personnels and patients affected the availability of drugs in RSUD (Province General Hospital) dr.Soedono Madiun. This research was conducted in RSUD dr.Soedono Madiun. Total sampling technique was used because of examining the entire population, namely all doctors and pharmacy personnels. The samples of patients were taken by using formula table from Issac and Michael. The independent variables were doctors, pharmacy personnels, and patients. The dependent variable was the availability of drugs. Data obtained by distributing questionnaires directly, then the data were analyzed by using linear regression from computer program, SPSS version 22. The result of R2 and F test was as follows: doctor factor was 0.706 and 69.562, pharmacist factor was 0710 and 114.962, and patient factor was 0.945 and 5660.020. The combined factors were 0.971 and 293.447. The study concludes that the doctor factor, pharmacist factor, or the patient factor significantly affects the availability of drugs. The combination of the three factors affect the availability of drugs at the time of JKN in RSUD dr.Soedono Madiun.